2022
DOI: 10.1038/s41598-022-23978-0
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on the experience of stigma for Chinese parents of children with autism spectrum disorder

Abstract: Experiencing stigma related to having a child with autism spectrum disorder (ASD) can be difficult and is detrimental to parent well-being. Since the research on stigmatized experiences among parents of children with ASD in non-Western communities is limited, this qualitative study examined the experiences, reactions and impacts of stigma on parents of children with ASD in Hong Kong. In-depth interviews were conducted with 54 Chinese parents/caregivers of children with ASD aged between 35 and 73 years old. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…34 The absence of social support and relative social isolation of parental caregivers, particularly those who left jobs to serve as primary caregivers, was also reported in this study. In agreement with findings in other chronic diseases, 35 our study demonstrated that stigmatization led parental caregivers to avoid social activities and social contact. Family stigma is prevalent in Chinese culture, which makes it even more difficult for parental caregivers of chronic diseases.…”
Section: Dovepresssupporting
confidence: 92%
“…34 The absence of social support and relative social isolation of parental caregivers, particularly those who left jobs to serve as primary caregivers, was also reported in this study. In agreement with findings in other chronic diseases, 35 our study demonstrated that stigmatization led parental caregivers to avoid social activities and social contact. Family stigma is prevalent in Chinese culture, which makes it even more difficult for parental caregivers of chronic diseases.…”
Section: Dovepresssupporting
confidence: 92%
“…We observe that professionals and the public must avoid stigmatizing caregivers. Professionals must be able to rapidly identify parental confidence deficits, emotions of despair, and social isolation and provide practical skills such as self-compassion and positive thinking approaches by constructing long-lasting support systems 58 60 . The public should also reflect critically on the correct attitudes, perceptions, and behaviors necessary to eliminate discriminatory behavior 61 .…”
Section: Discussionmentioning
confidence: 99%
“…It is also likely that they need to gain knowledge of people with autism and their parents to accurately identify stereotyped behavior as a dull habit. Some autistic people are conscious of their stereotypes and are compelled by societal pressure to imitate others intentionally 60 . We believe that in the early diagnosis stage, focus on screening children with family history and pay attention to premature attention disengagement, repetitive behaviors, and other risk signals in children 63 , 64 .…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the rational use of social support by parents of children with ASD, contributing to their life satisfaction (Hamama, 2023). While previous studies have reported the presence of government and organizational support for ASD, parents often hesitate to utilize these resources due to stigma and other reasons (Ng & Ng, 2022). This finding suggests that encouraging parents to seek and utilize support is essential in fostering a more supportive social environment for ASD families.…”
Section: Discussionmentioning
confidence: 99%